Monopsonistic Competition, Low-Wage Labour Markets, and Minimum Wages: An Empirical Analysis - Ronald Bachmann; Hanna Frings (Institute for the Study of Labor (IZA), 2016)
This paper investigates the degree of monopsony power of employers in different industries against the background of a statutory minimum wage introduction in Germany in January 2015. A semi-structural estimation approach is employed based on a dynamic model of monopsonistic competition. The empirical analysis relies on a linked employer-employee data set which allows to control for heterogeneity both on the worker and on the firm side. The results show important differences in monopsonistic competition among low-wage industries: While retailing, the hotel and restaurant industry as well as agriculture can be described as monopsonistic labour markets, this is not true for other services and manufacturing of food products. From a policy point of view, the introduction of a uniform minimum wage may therefore lead to different employment reactions in industries with a similar minimum wage bite.
Keywords: J42; J31; J38; 330; monopsony; minimum wage; low-wage industries; labor-supply elasticities; Germany